Dental Composites: Past, Present and Future - Amit Patodiya; Mithra N Hegde (Medsci Publications, 2012)
Composites have come a long way & have become a main stream material for as many restorative procedures as possible. This paper is an attempt to to portrait the developments from past to present & the future needs. Also it is an effort to highlight the properties which desirable to make this material free of any weakness. It can be concluded that composite resin is a promising aesthetic restorative material with universal application provided all its weak points are well taken care of.